Application of the Reliability Centred Maintenance Method at QGS in PT ABC Dumai - Melliana, Melliana (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
QGS A1 is a powerful crusher and dryer designed based on reference drying equipment with good performance efficiency. It has a very important function in expediting the production process, but this tool often breaks down, which really affects smooth production. In connection with the damage to the tool, it needs to be examined to find out what maintenance should be done. This study aims to find out earlier the damage that affects the smooth production so that it can be known what maintenance actions must be carried out. This study uses the Reliability-Centered Maintenance method, which utilizes information on reliability and weaknesses as well as a list of maintenance actions to choose from. The results of this study found a solution: the QGS A1 treatment run to failure was 81.2%, the direct condition was 18.18%, and the failure finding was 0%.